1993
DOI: 10.1136/gut.34.8.1038
|View full text |Cite
|
Sign up to set email alerts
|

Effect of eradication of Helicobacter pylori on gastric juice ascorbic acid concentrations.

Abstract: Ascorbic acid, the reduced form of vitamin C, may protect against gastric cancer and is secreted by the normal stomach. Secretion is impaired in Helicobacter pylori (H pylon) associated chronic gastritis. This study examined if eradication of H pylon improves gastric juice ascorbate values. Fasting gastric juice and plasma samples were collected at endoscopy from patients participating in trials of H pylori eradication for duodenal ulcer disease and intestinal metaplasia before and up to 15 months after attemp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
88
1
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(90 citation statements)
references
References 10 publications
0
88
1
1
Order By: Relevance
“…While activated, ROSreleasing phagocytic leukocytes recruited to the gastric mucosa during infection represent one obvious source of oxidative stress (21,79), other studies demonstrate that H. pylori itself also generates ROS (51) and that ROS accumulate in gastric epithelial cells (5,6,73). In addition, proinflammatory cytokines induce ROS in various cell types (47,48,61), and the decreased levels of ascorbic acid that are associated with H. pylori infection (64,71) also contribute to a pro-oxidative environment. H. pylori infection has been shown to increase expression and activity of spermine oxidase, which oxidizes polyamines that are abundant in epithelial cells to release hydrogen peroxide (77), suggesting another mechanism by which H. pylori induces oxidative stress.…”
mentioning
confidence: 99%
“…While activated, ROSreleasing phagocytic leukocytes recruited to the gastric mucosa during infection represent one obvious source of oxidative stress (21,79), other studies demonstrate that H. pylori itself also generates ROS (51) and that ROS accumulate in gastric epithelial cells (5,6,73). In addition, proinflammatory cytokines induce ROS in various cell types (47,48,61), and the decreased levels of ascorbic acid that are associated with H. pylori infection (64,71) also contribute to a pro-oxidative environment. H. pylori infection has been shown to increase expression and activity of spermine oxidase, which oxidizes polyamines that are abundant in epithelial cells to release hydrogen peroxide (77), suggesting another mechanism by which H. pylori induces oxidative stress.…”
mentioning
confidence: 99%
“…H. pylon-induced inflammation may facilitate gastric carcinogenesis by increasing the rate of cell replication. decreasing the concentration of ascorbic acid and inducing DNA damage via reactive oxygen species (Sobala et al 1993: Bechi et al 1996. It is worth noting that the prevalence of IM is also closely related to H. pylon infection (Rugge et al 1996).…”
mentioning
confidence: 99%
“…It was found that the eradication of Helicobacter pylori by metronidazole improves secretion of vitamin C (an antioxidant) into the gastric juice, which may lead to an increased protection against gastric cancer. 38 In addition, there has been luminal release of epidermal growth factor into the stomach in healthy subjects and in duodenal ulcer patients following triple therapy, which plays a crucial role in the duodenal ulcer healing process. 20 Furthermore, combined treatment with metronidazole has also shown a protection against platelet Ó 1997 Blackwell Science Ltd, Aliment Pharmacol Ther 11, 811±819 activating factor-induced shock and the resulting intestinal necrosis.…”
Section: Discussionmentioning
confidence: 99%